From Other Worlds : The Truth Behind Aliens, Abductions, UFOs and the Paranormal - Evans, Hilary, 1929-2011 (London Carlton Books, 1998)
A no-nonsense, authoritative view of the truth behind aliens, abductions and the paranormal, written by one of the United Kingdom's foremost experts on paranormal experiences.
Include Color Illustration and Index
Keywords: Unidentified flying objects -- Parapsychology--Investigation -- Spirits